An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M; Carrozzi, Marco; Skabar, Aldo; Sugden, David A; Barnett, Anna L; Henderson, Sheila E (Res Dev Disabil, 2019)
BACKGROUND: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. AIM: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. METHOD: A total of 718 Italian (IT) and 765 British (UK) children, aged 3-10 years, were individually tested on the age-appropriate items of the MABC-2 Test. RESULTS: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. CONCLUSION: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Non-invasive biomarkers of fetal brain development reflecting prenatal stress: An integrative multi-scale multi-species perspective on data collection and analysis. - Frasch, Martin G; Lobmaier, Silvia M; Stampalija, Tamara; Desplats, Paula; Pallarés, María Eugenia; Pastor, Verónica; Brocco, Marcela A; Wu, Hau-Tieng; Schulkin, Jay; Herry, Christophe L; Seely, Andrew J E; Metz, Gerlinde A S; et al. (Neurosci Biobehav Rev, 2018)
Prenatal stress (PS) impacts early postnatal behavioural and cognitive development. This process of 'fetal programming' is mediated by the effects of the prenatal experience on the developing hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). We derive a multi-scale multi-species approach to devising preclinical and clinical studies to identify early non-invasively available pre- and postnatal biomarkers of PS. The multiple scales include brain epigenome, metabolome, microbiome and the ANS activity gauged via an array of advanced non-invasively obtainable properties of fetal heart rate fluctuations. The proposed framework has the potential to reveal mechanistic links between maternal stress during pregnancy and changes across these physiological scales. Such biomarkers may hence be useful as early and non-invasive predictors of neurodevelopmental trajectories influenced by the PS as well as follow-up indicators of success of therapeutic interventions to correct such altered neurodevelopmental trajectories. PS studies must be conducted on multiple scales derived from concerted observations in multiple animal models and human cohorts performed in an interactive and iterative manner and deploying machine learning for data synthesis, identification and validation of the best non-invasive detection and follow-up biomarkers, a prerequisite for designing effective therapeutic interventions.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

What is the quality of the maternal near-miss case reviews in WHO European Region? Cross-sectional study in Armenia, Georgia, Latvia, Republic of Moldova and Uzbekistan. - Bacci, Alberta; Hodorogea, Stelian; Khachatryan, Henrik; Babojonova, Shohida; Irsa, Signe; Jansone, Maira; Dondiuc, Iurie; Matarazde, George; Lazdane, Gunta; Lazzerini, Marzia (BMJ Open, 2018)
OBJECTIVES: The maternal near-miss case review (NMCR) cycle is a type of clinical audit aiming at improving quality of maternal healthcare by discussing near-miss cases. In several countries this approach has been introduced and supported by WHO and partners since 2004, but information on the quality of its implementation is missing. This study aimed at evaluating the quality of the NMCR implementation in selected countries within WHO European Region. DESIGN: Cross-sectional study. SETTINGS: Twenty-three maternity units in Armenia, Georgia, Latvia, Moldova and Uzbekistan. ASSESSMENT TOOLS: A predefined checklist including 50 items, according to WHO methodology. Quality in the NMCR implementation was defined by summary scores ranging from 0 (totally inappropriate) to 3 (appropriate). RESULTS: Quality of the NMCR implementation was heterogeneous among different countries, and within the same country. Overall, the first part of the audit cycle (from case identification to case analysis) was fairly well performed (mean score 2.00, 95% CI 1.94 to 2.06), with the exception of the 'inclusion of users' views' (mean score 0.66, 95% CI 0.11 to 1.22), while the second part (developing recommendations, implementing them and ensuring quality) was poorly performed (mean score 0.66, 95% CI 0.11 to 1.22). Each country had at least one champion facility, where quality of the NMCR cycle was acceptable. Quality of the implementation was not associated with its duration. Gaps in implementation were of technical, organisational and attitudinal nature. CONCLUSIONS: Ensuring quality in the NMCR may be difficult but achievable. The high heterogeneity in results within the same country suggests that quality of the NMCR implementation depends, to a large extent, from hospital factors, including staff's commitment, managerial support and local coordination. Efforts should be put in preventing and mitigating common barriers that hamper successful NMCR implementation.
Keywords: Armenia; Checklist; Cross-Sectional Studies; Female; Georgia; Humans; Latvia; Maternal Mortality; Medical Audit; Moldova; Near Miss, Healthcare; Pregnancy; Pregnancy Complications; Quality Improvement; Uzbekistan

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Antibiotic Prophylaxis for Urinary Tract Infection-Related Renal Scarring: A Systematic Review. - Hewitt, Ian K; Pennesi, Marco; Morello, William; Ronfani, Luca; Montini, Giovanni (Pediatrics, 2017)
CONTEXT: Acute pyelonephritis may result in renal scarring. Recent prospective studies have shown a small benefit of antibiotic prophylaxis in preventing symptomatic and febrile urinary tract infections (UTIs), while being underpowered to detect any influence in prevention of renal damage. OBJECTIVES: Review of the literature and a meta-analysis to evaluate the effect of antibiotic prophylaxis on UTI-related renal scarring. DATA SOURCES: Medline, Embase, and Cochrane Controlled Trials Register electronic databases were searched for studies published in any language and bibliographies of identified prospective randomized controlled trials (RCTs) performed and published between 1946 and August 2016. STUDY SELECTION: Subjects 18 years of age or younger with symptomatic or febrile UTIs, enrolled in prospective RCTs of antibiotic prophylaxis where Tc dimercaptosuccinic acid scans were performed at entry into the study and at late follow-up to detect new scar formation. DATA EXTRACTION: The literature search, study characteristics, inclusion and exclusion criteria, and risk of bias assessment were independently evaluated by 2 authors. RESULTS: Seven RCTs (1427 subjects) were included in the meta-analysis. Our results show no influence of antibiotic prophylaxis in preventing renal scarring (pooled risk ratio, 0.83; 95% confidence interval, 0.55-1.26) as did a subanalysis restricted to those subjects with vesicoureteral reflux (pooled risk ratio, 0.79; 95% confidence interval, 0.51-1.24). LIMITATIONS: Limitations include the small number of studies, short duration of follow-up, and insufficient children with high-grade dilating reflux and/or renal dysplasia enrolled in the studies. CONCLUSIONS: Antibiotic prophylaxis is not indicated for the prevention of renal scarring after a first or second symptomatic or febrile UTI in otherwise healthy children.
Keywords: Acute Disease; Antibiotic Prophylaxis; Child; Cicatrix; Humans; Kidney; Pyelonephritis; Urinary Tract Infections

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Climate change, emerging infections and blood donations. - Cegolon, L; Heymann, W C; Lange, J H (J Travel Med, 2017)
Keywords: Blood Transfusion; Climate Change; Communicable Diseases, Emerging; Global Health; Humans; Travel

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

Early-life nutritional exposures and lifelong health: immediate and long-lasting impacts of probiotics, vitamin D, and breastfeeding. - Berti, Cristiana; Agostoni, Carlo; Davanzo, Riccardo; Hyppönen, Elina; Isolauri, Erika; Meltzer, Helle M; Steegers-Theunissen, Régine P M; Cetin, Irene (Nutr Rev, 2017)
Pregnancy and infancy comprise the most critical stages for conditioning an individual's health, with a number of implications for subsequent risks of morbidity, mortality, and reproductive health. Nutrition may influence both the overall pregnancy outcome and the growth trajectory and immune system of the fetus and infant, with short- and long-term effects on the health of the offspring. Within this context, leading experts at Expo Milano 2015 in Milan, Italy, discussed up-to-date knowledge while providing suggestions and challenges before, during, and after pregnancy. This narrative review summarizes the key issues raised by the experts concerning the interplay between the nutritional environment from conception to early infancy and the offspring's immediate and lifelong health, with a particular focus on epigenetic mechanisms, probiotics, vitamin D, and breastfeeding. Taken together, the findings strengthen the awareness that nutritional exposures occurring from preconception to the postnatal period may be strong determinants of the offspring's health and may provide supportive evidence for current nutritional recommendations and guidelines for pregnant women and infants. Critical topics to be addressed in future research and translated into recommendations of public health relevance are also highlighted.
Keywords: Breast Feeding; Diet; Female; Humans; Infant; Infant Nutritional Physiological Phenomena; Meta-Analysis as Topic; Nutritional Status; Pregnancy; Pregnancy Outcome; Probiotics; Vitamin D

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

Genetic structure in the Sherpa and neighboring Nepalese populations. - Cole, Amy M; Cox, Sean; Jeong, Choongwon; Petousi, Nayia; Aryal, Dhana R; Droma, Yunden; Hanaoka, Masayuki; Ota, Masao; Kobayashi, Nobumitsu; Gasparini, Paolo; Montgomery, Hugh; Robbins, Peter; et al. (BMC Genomics, 2017)
BACKGROUND: We set out to describe the fine-scale population structure across the Eastern region of Nepal. To date there is relatively little known about the genetic structure of the Sherpa residing in Nepal and their genetic relationship with the Nepalese. We assembled dense genotype data from a total of 1245 individuals representing Nepal and a variety of different populations resident across the greater Himalayan region including Tibet, China, India, Pakistan, Kazakhstan, Uzbekistan, Tajikistan and Kirghizstan. We performed analysis of principal components, admixture and homozygosity. RESULTS: We identified clear substructure across populations resident in the Himalayan arc, with genetic structure broadly mirroring geographical features of the region. Ethnic subgroups within Nepal show distinct genetic structure, on both admixture and principal component analysis. We detected differential proportions of ancestry from northern Himalayan populations across Nepalese subgroups, with the Nepalese Rai, Magar and Tamang carrying the greatest proportions of Tibetan ancestry. CONCLUSIONS: We show that populations dwelling on the Himalayan plateau have had a clear impact on the Northern Indian gene pool. We illustrate how the Sherpa are a remarkably isolated population, with little gene flow from surrounding Nepalese populations.
Keywords: Asian Continental Ancestry Group; Chromosomes, Human, Y; DNA; DNA, Mitochondrial; Ethnic Groups; Gene Flow; Genotype; Humans; Leukocytes; Likelihood Functions; Nepal; Principal Component Analysis

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Immediate delivery or expectant management in gestational diabetes at term: the GINEXMAL randomised controlled trial. - Alberico, S; Erenbourg, A; Hod, M; Yogev, Y; Hadar, E; Neri, F; Ronfani, L; Maso, G (BJOG, 2017)
OBJECTIVE: To evaluate maternal and perinatal outcomes after induction of labour versus expectant management in pregnant women with gestational diabetes at term. DESIGN: Multicentre open-label randomised controlled trial. SETTING: Eight teaching hospitals in Italy, Slovenia, and Israel. SAMPLE: Singleton pregnancy, diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria (IADPSGC), between 38 and 39 weeks of gestation, without other maternal or fetal conditions. METHODS: Patients were randomly assigned to induction of labour or expectant management and intensive follow-up. Data were analysed by 'intention to treat'. MAIN OUTCOME MEASURES: The primary outcome was incidence of caesarean section. Secondary outcomes were maternal and perinatal mortality and morbidity. RESULTS: A total of 425 women were randomised to the study groups. The incidence of caesarean section was 12.6% in the induction group versus 11.7% in the expectant group. No difference was found between the two groups (relative risk, RR 1.06; 95% confidence interval, 95% CI 0.64-1.77; P = 0.81). The incidence of non-spontaneous delivery, either by caesarean section or by operative vaginal delivery, was 21.0 and 22.3%, respectively (RR 0.94; 95% CI 0.66-1.36; P = 0.76). Neither maternal nor fetal deaths occurred. The few cases of shoulder dystocia were solved without any significant birth trauma. CONCLUSIONS: In women with gestational diabetes, without other maternal or fetal conditions, no difference was detected in birth outcomes regardless of the approach used (i.e. active versus expectant management). Although the study was underpowered, the magnitude of the between-group difference was very small and without clinical relevance. TWEETABLE ABSTRACT: Immediate delivery or expectant management in gestational diabetes at term?
Keywords: Adult; Delivery, Obstetric; Diabetes, Gestational; Female; Humans; Infant, Newborn; Israel; Italy; Maternal Mortality; Perinatal Mortality; Pregnancy; Pregnancy Outcome; Slovenia; Term Birth; Watchful Waiting

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Targeted sequencing identifies novel variants involved in autosomal recessive hereditary hearing loss in Qatari families. - Alkowari, Moza K; Vozzi, Diego; Bhagat, Shruti; Krishnamoorthy, Navaneethakrishnan; Morgan, Anna; Hayder, Yousra; Logendra, Barathy; Najjar, Nehal; Gandin, Ilaria; Gasparini, Paolo; Badii, Ramin; Girotto, Giorgia; et al. (Mutat Res, 2017)
Hereditary hearing loss is characterized by a very high genetic heterogeneity. In the Qatari population the role of GJB2, the worldwide HHL major player, seems to be quite limited compared to Caucasian populations. In this study we analysed 18 Qatari families affected by non-syndromic hearing loss using a targeted sequencing approach that allowed us to analyse 81 genes simultaneously. Thanks to this approach, 50% of these families (9 out of 18) resulted positive for the presence of likely causative alleles in 6 different genes: CDH23, MYO6, GJB6, OTOF, TMC1 and OTOA. In particular, 4 novel alleles were detected while the remaining ones were already described to be associated to HHL in other ethnic groups. Molecular modelling has been used to further investigate the role of novel alleles identified in CDH23 and TMC1 genes demonstrating their crucial role in Ca2+ binding and therefore possible functional role in proteins. Present study showed that an accurate molecular diagnosis based on next generation sequencing technologies might largely improve molecular diagnostics outcome leading to benefits for both genetic counseling and definition of recurrence risk.
Keywords: Adolescent; Alleles; Cadherins; Child; Child, Preschool; Connexins; Female; GPI-Linked Proteins; Hearing Loss, Sensorineural; Humans; Infant; Male; Membrane Proteins; Models, Molecular; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Qatar; Sequence Analysis, DNA

Training in Occupational Medicine: Jurisprudential Malfunctions in the Italian System and European Perspectives. - Cegolon, L; Heymann, W C; Xodo, C; Lange, J H (Ann Ig, 2017)
BACKGROUND: To practice occupational health in Europe, a medical doctor must qualify in occupational medicine. This requires a period of postgraduate specialist medical training lasting a minimum of four years, in conformity with European regulations, to obtain a certificate of completion of training which is then mutually recognized within the entire European Union. DISCUSSION: In 2002 an Italian law allowed doctors specialized in public health medicine and legal/forensic medicine to also practice as consultants in occupational medicine in the country. However a subsequent law in 2008 determined that only physicians specialized in occupational medicine could freely practice as consultants in this discipline. The other two categories (consultants in public health medicine and consultants in legal/forensic medicine) were required to undertake additional training (a Master course) to qualify as consultants in occupational medicine. CONCLUSIONS: Doctors who entered postgraduate training in public health or legal/forensic medicine before 2008, with the option to practice also as consultants in occupational medicine upon completion of their training, suffered an unprecedented and legally questionable retroactive application of this new law which stripped them of previously acquired rights. Moreover, even after qualifying by undertaking this extra training in occupational medicine, the latter two categories of doctors do not have their training recognized in other member states of the European Union. To disallow the rights of doctors qualified in occupational medicine to work as consultants in the latter medical discipline elsewhere within the European Union seems a clear violation of professional rights and, as such, legal action could be taken to submit this issue to European attention.
Keywords: Certification; European Union; Italy; Occupational Medicine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Association between p21 Ser31Arg polymorphism and the development of cervical lesion in women infected with high risk HPV. - Lima, Géssica; Santos, Erinaldo; Angelo, Hildson; Oliveira, Micheline; Heráclio, Sandra; Leite, Fernanda; de Melo, Celso; Crovella, Sergio; Maia, Maria; Souza, Paulo (Tumour Biol, 2016)
Infection by high-risk human papillomavirus (HR-HPV) and single nucleotide polymorphism (SNP) in genes involved in cell cycle control, as p21 and p27, are important factors in the development of different types of human cancers. This study aims at investigating whether both the p21 Ser31Arg and p27 V109G polymorphisms are associated with susceptibility to the development of cervical lesions in women HR-HPV positive. We analyzed 132 women HPV positive and with cervical lesions or CC and 154 healthy control (HPV negative and without cervical lesions). p21 Ser31Arg and p27 V109G polymorphisms were analyzed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and sequencing. The p21 31Arg allele was associated with susceptibility for the development of cervical lesions (P* = 0.0009), while p27 V109G polymorphism showed no significant differences for this association (P* = 0.89). However, the combined effect of the polymorphisms showed that the presence of the CC genotype (SNP p21 Ser31Arg) conferred protection for the development of cervical lesions (OR = 0.39). p21 Ser31Arg and p27 V109G polymorphisms were not associated with the grade of cervical lesions (CINI, CINII, and CINIII) or CC (P* > 0.05). The HR-HPV more frequent in this study were of 16 (57.6 %) and 18 (37.1 %) types; however, no association was observed when both polymorphisms and risk factors analyzed were compared (P* > 0.05). Our findings suggest a possible association between p21 Ser31tabArg polymorphism and susceptibility to the development of cervical lesions in women from Pernambuco. Brazil.

CCR2 and CCR5 genes polymorphisms in women with cervical lesions from Pernambuco, Northeast Region of Brazil: a case-control study. - Santos, Erinaldo Ubirajara Damasceno Dos; Lima, Géssica Dayane Cordeiro de; Oliveira, Micheline de Lucena; Heráclio, Sandra de Andrade; Silva, Hildson Dornelas Angelo da; Crovella, Sergio; Maia, Maria de Mascena Diniz; Souza, Paulo Roberto Eleutério de (Mem Inst Oswaldo Cruz, 2016)
Polymorphisms in chemokine receptors play an important role in the progression of cervical intraepithelial neoplasia (CIN) to cervical cancer (CC). Our study examined the association of CCR2-64I (rs1799864) andCCR5-Δ32 (rs333) polymorphisms with susceptibility to develop cervical lesion (CIN and CC) in a Brazilian population. The genotyping of 139 women with cervical lesions and 151 women without cervical lesions for the CCR2-64I and CCR5-Δ32 polymorphisms were performed using polymerase chain reaction-restriction fragment length polymorphism. The individuals carrying heterozygous or homozygous genotypes (GA+AA) for CCR2-64I polymorphisms seem to be at lower risk for cervical lesion [odds ratio (OR) = 0.37, p = 0.0008)]. The same was observed for the A allele (OR = 0.39, p = 0.0002), while no association was detected (p > 0.05) with CCR5-Δ32 polymorphism. Regarding the human papillomavirus (HPV) type, patients carrying the CCR2-64Ipolymorphism were protected against infection by HPV type 16 (OR = 0.35, p = 0.0184). In summary, our study showed a protective effect ofCCR2-64I rs1799864 polymorphism against the development of cervical lesions (CIN and CC) and in the susceptibility of HPV 16 infection.

Circulating levels of TNF-related apoptosis inducing-ligand are decreased in patients with large adult-type granulosa cell tumors-implications for therapeutic potential. - Färkkilä, Anniina; Zauli, Giorgio; Haltia, Ulla-Maija; Pihlajoki, Marjut; Unkila-Kallio, Leila; Secchiero, Paola; Heikinheimo, Markku (Tumour Biol, 2016)
Targeted treatments are needed for advanced adult-type granulosa cell tumors (AGCTs). We set out to assess tumor tissue and circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a promising anti-cancer cytokine, in patients affected by AGCT. We analyzed tissue expression of TRAIL in 127 AGCTs using immunohistochemistry or RT-PCR. Soluble TRAIL was measured by means of ELISA from 141 AGCT patient serum samples, as well as the conditioned media of 15 AGCT patient-derived primary cell cultures, and the KGN cell line. Tissue and serum TRAIL levels were analyzed in relationship with clinical parameters, and serum estradiol, FSH, and LH levels. We found that AGCT samples expressed TRAIL mRNA and protein at levels comparable to normal granulosa cells. AGCT cells did not release soluble TRAIL. TRAIL protein levels were decreased in tumors over 10 cm in diameter (p = 0.04). Consistently, circulating TRAIL levels correlated negatively to tumor dimension (p = 0.01). Circulating TRAIL levels negatively associated with serum estradiol levels. In multiple regression analysis, tumor size was an independent factor contributing to the decreased levels of soluble TRAIL in AGCT patients. AGCTs associate with significantly decreased tumor tissue and serum TRAIL levels in patients with a large tumor mass. These findings encourage further study of agonistic TRAIL treatments in patients with advanced or recurrent AGCT.

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

Abnormal cytoplasmic extensions associated with active αIIbβ3 are probably the cause for macrothrombocytopenia in Glanzmann thrombasthenia-like syndrome. - Hauschner, Hagit; Mor-Cohen, Ronit; Messineo, Stefania; Mansour, Wissam; Seligsohn, Uri; Savoia, Anna; Rosenberg, Nurit (Blood Coagul Fibrinolysis, 2015)
Mutations in the ITGA2B or ITGB3 genes that encode for the αIIbβ3 platelet integrin usually cause Glanzmann thrombasthenia, a severe autosomal recessive bleeding disorder characterized by absence of platelet aggregation, but normal platelet number and size. Several rare mutations cause a Glanzmann-like syndrome which manifests macrothrombocytopenia and usually displays autosomal dominant inheritance. The exact mechanism causing Glanzmann-like syndrome is unknown. One typical example of Glanzmann-like mutations causes deletion of 40 amino acids (p.647-686) in the β3 β-tail domain (βTD_del) that was found in the heterozygous state in Italian and Japanese families. A second example is a missense mutation, C560R, located in the epidermal growth factor-like domain, found in the homozygous state in a French patient. Both mutations cause constitutive activation of αIIbβ3, but differ in their surface expression. In the current study, we generated cultured cells expressing β3-βTD_del or β3-C560R mutations along with wild-type αIIb, and examined the cells' ability to create tubulin-dependent protrusions compared to cells expressing wild-type αIIbβ3. Unlike cells expressing wild-type αIIbβ3, cells harboring each of the mutations exhibited abnormal cytoplasmic extensions on immobilized fibrinogen or Von Willebrand factor, which resembled extensions formed in megakaryocyte leading to proplatelets. Moreover, we showed that formation of abnormal extensions occurred also in wild-type αIIbβ3 cells when activated by activating antibody. These results suggest that the active conformation of αIIbβ3 can induce cytoskeletal rearrangements that lead to impaired proplatelet formation.
Keywords: Animals; Cell Line; Cricetinae; Cytoskeleton; DNA, Complementary; Fibrinogen; Genetic Vectors; Humans; Integrin alpha2; Integrin beta3; Megakaryocytes; Mesocricetus; Microtubules; Mutation, Missense; Platelet Glycoprotein GPIIb-IIIa Complex; Protein Conformation; Protein Interaction Mapping; Protein Structure, Tertiary; Recombinant Fusion Proteins; Sequence Deletion; Thrombasthenia; Tubulin; von Willebrand Factor

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Genetic evidence for an origin of the Armenians from Bronze Age mixing of multiple populations. - Haber, Marc; Mezzavilla, Massimo; Xue, Yali; Comas, David; Gasparini, Paolo; Zalloua, Pierre; Tyler-Smith, Chris (Eur J Hum Genet, 2015)
The Armenians are a culturally isolated population who historically inhabited a region in the Near East bounded by the Mediterranean and Black seas and the Caucasus, but remain under-represented in genetic studies and have a complex history including a major geographic displacement during World War I. Here, we analyse genome-wide variation in 173 Armenians and compare them with 78 other worldwide populations. We find that Armenians form a distinctive cluster linking the Near East, Europe, and the Caucasus. We show that Armenian diversity can be explained by several mixtures of Eurasian populations that occurred between ~3000 and ~2000 bce, a period characterized by major population migrations after the domestication of the horse, appearance of chariots, and the rise of advanced civilizations in the Near East. However, genetic signals of population mixture cease after ~1200 bce when Bronze Age civilizations in the Eastern Mediterranean world suddenly and violently collapsed. Armenians have since remained isolated and genetic structure within the population developed ~500 years ago when Armenia was divided between the Ottomans and the Safavid Empire in Iran. Finally, we show that Armenians have higher genetic affinity to Neolithic Europeans than other present-day Near Easterners, and that 29% of Armenian ancestry may originate from an ancestral population that is best represented by Neolithic Europeans.European Journal of Human Genetics advance online publication, 21 October 2015; doi:10.1038/ejhg.2015.206.

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Insights from Cardiac Mechanics after Three Decades from Successfully Repaired Aortic Coarctation. - Faganello, Giorgio; Fisicaro, Maurizio; Russo, Giulia; Iorio, Anita; Mazzone, Carmine; Grande, Eliana; Humar, Franco; Cherubini, Antonella; Pandullo, Claudio; Barbati, Giulia; Tarantini, Luigi; Benettoni, Alessandra; et al. (Congenit Heart Dis, 2015)
BACKGROUND AND AIMS: Patients who underwent a successful repair of the aortic coarctation show chronic hyperdynamic state and normal left ventricular (LV) geometry; however, there are few data regarding the LV systolic function in the long term. Accordingly, we assessed LV systolic mechanics and factors associated with LV systolic dysfunction (LVSD) in patients with repaired CoA. METHODS: Clinical and echocardiographic data from 19 repaired CoA were analyzed 28 ± 13 years after surgery. Stress-corrected midwall shortening (sc-MS) and mitral annular peak systolic velocity (S') were analyzed as indexes of LV circumferential and longitudinal systolic function, respectively. Echocardiographic data of CoA patients were compared with 19 patients matched for age and hypertension and 38 healthy controls. Sc-MS was considered impaired if <89%, S' if <8.5 cm/s (10th percentiles of healthy controls, respectively). RESULTS: There were no statistical differences between study groups in LV volumes, mass and geometry. LV ejection fraction and Sc-MS were similar in all groups, however, CoA group had a significantly lower peak S' in comparison with matched and healthy controls (7.1 ± 1.3, 10.3 ± 1.9, and 11.1 ± 1.5, respectively; all P < 0.001). Prevalence of longitudinal LVSD defined as low S' was 84% in CoA, 13% in matched, and 5% in healthy control group (all P<0.05). Multivariate logistic regression analysis revealed that low peak S' was independently related to higher E/E' ratio and the presence of CoA. CONCLUSIONS: Patients who underwent a successful repair of CoA commonly show asymptomatic longitudinal LVSD associated with worse LV diastolic function in the long-term follow-up.

The Kalash genetic isolate: ancient divergence, drift, and selection. - Ayub, Qasim; Mezzavilla, Massimo; Pagani, Luca; Haber, Marc; Mohyuddin, Aisha; Khaliq, Shagufta; Mehdi, Syed Qasim; Tyler-Smith, Chris (Am J Hum Genet, 2015)
The Kalash represent an enigmatic isolated population of Indo-European speakers who have been living for centuries in the Hindu Kush mountain ranges of present-day Pakistan. Previous Y chromosome and mitochondrial DNA markers provided no support for their claimed Greek descent following Alexander III of Macedon's invasion of this region, and analysis of autosomal loci provided evidence of a strong genetic bottleneck. To understand their origins and demography further, we genotyped 23 unrelated Kalash samples on the Illumina HumanOmni2.5M-8 BeadChip and sequenced one male individual at high coverage on an Illumina HiSeq 2000. Comparison with published data from ancient hunter-gatherers and European farmers showed that the Kalash share genetic drift with the Paleolithic Siberian hunter-gatherers and might represent an extremely drifted ancient northern Eurasian population that also contributed to European and Near Eastern ancestry. Since the split from other South Asian populations, the Kalash have maintained a low long-term effective population size (2,319-2,603) and experienced no detectable gene flow from their geographic neighbors in Pakistan or from other extant Eurasian populations. The mean time of divergence between the Kalash and other populations currently residing in this region was estimated to be 11,800 (95% confidence interval = 10,600-12,600) years ago, and thus they represent present-day descendants of some of the earliest migrants into the Indian sub-continent from West Asia.
Keywords: Asia; Asian Continental Ancestry Group; Chromosomes, Human, Y; Demography; DNA, Mitochondrial; European Continental Ancestry Group; Genetic Drift; Genetics, Population; Haplotypes; History, Ancient; Humans; Male; Pakistan; Phylogeny

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

MID2 can substitute for MID1 and control exocytosis of lytic granules in cytotoxic T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Levring, Trine B; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte M; Geisler, Carsten (APMIS, 2015)
We have recently shown that the E3 ubiquitin ligase midline 1 (MID1) is upregulated in murine cytotoxic lymphocytes (CTL), where it controls exocytosis of lytic granules and the killing capacity. Accordingly, CTL from MID1 knock-out (MID1(-/-)) mice have a 25-30% reduction in exocytosis of lytic granules and cytotoxicity compared to CTL from wild-type (WT) mice. We wondered why the MID1 gene knock-out did not affect exocytosis and cytotoxicity more severely and speculated whether MID2, a close homologue of MID1, might partially compensate for the loss of MID1 in MID1(-/-) CTL. Here, we showed that MID2, like MID1, is upregulated in activated murine T cells. Furthermore, MID1(-/-) CTL upregulated MID2 two-twenty-fold stronger than CTL from WT mice, suggesting that MID2 might compensate for MID1. In agreement, transfection of MID2 into MID1(-/-) CTL completely rescued exocytosis of lytic granules in MID1(-/-) CTL, and vice versa, knock-down of MID2 inhibited exocytosis of lytic granules in both WT and MID1(-/-) CTL, demonstrating that both MID1 and MID2 play a central role in the regulation of granule exocytosis and that functional redundancy exists between MID1 and MID2 in CTL.
Keywords: Animals; Cytoplasmic Granules; Exocytosis; Interferon-gamma; Mice; Mice, Inbred C57BL; Mice, Knockout; Microtubule-Associated Proteins; Proteins; T-Lymphocytes, Cytotoxic; Transcription Factors; Up-Regulation

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

A Sensitive Electrochemiluminescence Immunosensor for Celiac Disease Diagnosis Based on Nanoelectrode Ensembles. - Habtamu, Henok B; Sentic, Milica; Silvestrini, Morena; De Leo, Luigina; Not, Tarcisio; Arbault, Stephane; Manojlovic, Dragan; Sojic, Neso; Ugo, Paolo (Anal Chem, 2015)

Tumor necrosis factor (TNF) alpha and interleukin (IL) 18 genes polymorphisms are correlated with susceptibility to HPV infection in patients with and without cervical intraepithelial lesion. - Tavares, Mayara C Mansur; de Lima Júnior, Sérgio F; Coelho, Antonio V C; Marques, Trícia Ruschelle N M; de Araújo, Diêgo Henrique T; Heráclio, Sandra de A; Amorim, Melânia M Ramos; de Souza, Paulo Roberto E; Crovella, Sergio (Ann Hum Biol, 2015)
BACKGROUND: The Human Papillomavirus (HPV) predisposes 500 000 women to cervical cancer. Host genetic background may facilitate virus persistence in the uterine cervix. Polymorphisms in regulatory and coding regions of cytokine genes have been associated with susceptibility to some human diseases. AIM: This study aims at investigating whether TNFA -308 G/A and IL18 -137 G/C and -607 C/A polymorphisms are associated with susceptibility to HPV infection/progression to high-grade squamous intraepithelial lesion (HSIL). SUBJECTS AND METHODS: One hundred and twenty-two HPV infected and 132 HPV negative women (the latter used as healthy controls) were analysed. TNFA -308 G/A and IL18 (-137G/C and -607 C/A) polymorphisms were analysed using specific sequence polymorphism PCR (SSP-PCR). Univariate statistical analysis and a logistic regression were performed. RESULTS: The TNFA -308A allele was associated with susceptibility to HPV infection (p = 0.0008), while the IL18 -607A allele conferred protection against HPV infection (p = 0.0043). TNFA -308 G/A and IL18 (-137G/C and -607 C/A) polymorphisms were not associated with development of cervical lesions (p > 0.05). An association was also observed between smoking and susceptibility to the development of HSIL. CONCLUSION: The findings suggest an association between two TNFA SNPs and susceptibility to HPV infection in women from Northeast Brazil. The results need to be functionally validated and replicated in other populations with different ethnic backgrounds.

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Human recombinant lysozyme downregulates advanced glycation endproduct-induced interleukin-6 production and release in an in-vitro model of human proximal tubular epithelial cells. - Gallo, Davide; Cocchietto, Moreno; Masat, Elisa; Agostinis, Chiara; Harei, Elisa; Veronesi, Paolo; Sava, Gianni (Exp Biol Med (Maywood), 2014)
Diabetic nephropathy is the leading cause of chronic renal disease and one of the major causes of cardiovascular mortality. Evidence suggests that its progression is due to the chronic hyperglycemia consequent to the production and accumulation of advanced glycation endproducts (AGEs). Lysozyme was shown to posses AGE-sequestering properties and the capacity to reduce the severity of the early stage manifestations of the diabetic nephropathy. This study was aimed to contribute to the understanding the molecular mechanisms of lysozyme effectiveness in the diabetic nephropathy, using an in-vitro cellular model, represented by the HK-2 cells, human proximal tubular epithelial cells. Lysozyme significantly reduced the AGE-induced IL-6 mRNA and an ELISA assay showed also a decreased release of the functional protein with a dose-dependent trend. In addition, lysozyme prevented macrophage recruitment, suggesting its capacity to elicit an anti-inflammatory action. We may conclude that the protective action of lysozyme on the nephrotoxic effects of AGE may depend, at least in part, on its ability to prevent the production and release of inflammatory mediators, such as IL-6 and to reduce macrophage recruitment in the inflammatory sites.
Keywords: Cell Line; Cell Movement; Cell Survival; Chemokine CX3CL1; Diabetic Nephropathies; Down-Regulation; Epithelial Cells; Glycosylation End Products, Advanced; Humans; Inflammation Mediators; Interleukin-18; Interleukin-6; Kidney Tubules, Proximal; Macrophage Activation; Macrophages; Muramidase; Recombinant Proteins; RNA, Messenger; Tumor Necrosis Factor-alpha; U937 Cells

Midline 1 directs lytic granule exocytosis and cytotoxicity of mouse killer T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Johansen, Bo B; Braunstein, Thomas H; Bonefeld, Charlotte M; Kongsbak, Martin; Jensen, Benjamin A H; Woetmann, Anders; Thomsen, Allan R; Odum, Niels; von Essen, Marina R; et al. (Eur J Immunol, 2014)
Midline 1 (MID1) is a microtubule-associated ubiquitin ligase that regulates protein phosphatase 2A activity. Loss-of-function mutations in MID1 lead to the X-linked Opitz G/BBB syndrome characterized by defective midline development during embryogenesis. Here, we show that MID1 is strongly upregulated in murine cytotoxic lymphocytes (CTLs), and that it controls TCR signaling, centrosome trafficking, and exocytosis of lytic granules. In accordance, we find that the killing capacity of MID1(-/-) CTLs is impaired. Transfection of MID1 into MID1(-/-) CTLs completely rescued lytic granule exocytosis, and vice versa, knockdown of MID1 inhibited exocytosis of lytic granules in WT CTLs, cementing a central role for MID1 in the regulation of granule exocytosis. Thus, MID1 orchestrates multiple events in CTL responses, adding a novel level of regulation to CTL activation and cytotoxicity.
Keywords: Animals; Blotting, Western; Cytotoxicity, Immunologic; Exocytosis; Flow Cytometry; Mice; Mice, Knockout; Mice, Transgenic; Proteins; Reverse Transcriptase Polymerase Chain Reaction; Secretory Vesicles; T-Lymphocytes, Cytotoxic

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

Accuracy of diagnostic antibody tests for coeliac disease in children: summary of an evidence report. - Giersiepen, Klaus; Lelgemann, Monika; Stuhldreher, Nina; Ronfani, Luca; Husby, Steffen; Koletzko, Sibylle; Korponay-Szabó, Ilma R (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: The aim of this study was to summarise the evidence from 2004 to September 2009 on the performance of laboratory-based serological and point of care (POC) tests for diagnosing coeliac disease (CD) in children using histology as reference standard. PATIENTS AND METHODS: We searched MEDLINE and EMBASE for studies reporting on children for tests based on IgA and IgG anti-gliadin (AGA), endomysial (EmA), anti-transglutaminase-2 (TG2), and anti-deamidated gliadin peptides (DGP) antibodies or POC tests. For inclusion, histological analysis of duodenal biopsies and sensitivity and specificity for index tests had to be reported. Data were pooled and summary measures calculated for sensitivity, specificity, positive and negative likelihood ratios ("LR+", "LR-"), and diagnostic odds ratios (DOR). In case of elevated statistical heterogeneity, studies reaching 90% sensitivity or specificity were reported. RESULTS: A total of 2510 articles were reviewed; 16 entered meta-analysis, reporting on 3110 patients (1876 with CD, 1234 without CD). For IgA-EmA, sensitivity was ≥90% in 7/11 studies and pooled specificity 98.2%. For IgA-anti-TG2, 11/15 studies yielded sensitivities ≥90% and 13/15 specificities ≥90%. For IgA-DGP, sensitivity ranged between 80.7% and 95.1% (specificity 86.3%-93.1%); for IgG-DGP between 80.1% and 98.6% (specificity 86.0-96.9%). IgA-EmA had the highest pooled DOR (554) and LR+ (31.8) for a laboratory test, followed by IgA-anti-TG2, IgG-DGP, IgA-DGP and IgA-AGA. POC tests showed a pooled sensitivity of 96.4% for IgA-TG2 (specificity 97.7%). CONCLUSIONS: IgA-EmA and IgA-anti-TG2 tests appear highly accurate to diagnose CD. IgG-anti-DGP tests may help in excluding CD. IgA-AGA and IgA-DGP tests show inferior accuracy. POC tests may achieve high accuracy in the hands of experienced readers, but IgA-anti-TG2/EmA were superior.
Keywords: Autoantibodies; Biological Markers; Celiac Disease; Child; Gliadin; GTP-Binding Proteins; Humans; Immunoglobulin A; Immunoglobulin G; Point-of-Care Systems; Sensitivity and Specificity; Transglutaminases

Coeliac disease diagnosis: ESPGHAN 1990 criteria or need for a change? Results of a questionnaire. - Ribes-Koninckx, C; Mearin, M L; Korponay-Szabó, I R; Shamir, R; Husby, S; Ventura, A; Branski, D; Catassi, C; Koletzko, S; Mäki, M; Troncone, R; Zimmer, K P (J Pediatr Gastroenterol Nutr, 2012)
BACKGROUND AND OBJECTIVES: A revision of criteria for diagnosing coeliac disease (CD) is being conducted by The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN). In parallel, we have performed a survey aimed to evaluate present practices for CD among paediatric gastroenterologists and to learn their views on the need for modification of present criteria for CD diagnosis. PATIENTS AND METHODS: Questionnaires were distributed to experienced paediatric gastroenterologists (ESPGHAN members) via the Internet. RESULTS: Overall, 95 valid questionnaires were available for analysis, pertaining to 28 different countries, with the majority of responders treating patients with CD for >15 years. Only about 12% of the responders comply with present criteria, noncompliance being related mainly to the challenge policy. Approximately 90% request a revision and modification of the present criteria. Forty-four percent want to omit the small bowel biopsy in symptomatic children with positive anti-tissue transglutaminase immunoglobulin (Ig) A or endomysial IgA antibodies, especially if they are DQ2/DQ8 positive. For silent cases detected by screening with convincingly positive anti-tissue transglutaminase IgA or EMA IgA, about 30% consider that no small bowel biopsy should be required in selected cases. Adding human leukocyte antigen typing in the diagnostic workup was asked for by 42% of the responders. As for gluten challenge, a new policy is advocated restricting its obligation to cases whenever the diagnosis is doubtful or unclear. CONCLUSIONS: Based on these opinions, revision of the ESPGHAN criteria for diagnosing CD is urgently needed.
Keywords: Adolescent; Adult; Biopsy; Celiac Disease; Child; Child, Preschool; Glutens; Guideline Adherence; Guidelines as Topic; Health Care Surveys; Humans; Immunoglobulin A; Intestine, Small; Physician's Practice Patterns; Questionnaires; Societies, Medical; Transglutaminases; Young Adult

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. - Snowden, J A; Saccardi, R; Allez, M; Ardizzone, S; Arnold, R; Cervera, R; Denton, C; Hawkey, C; Labopin, M; Mancardi, G; Martin, R; Moore, J J; et al. (Bone Marrow Transplant, 2012)
In 1997, the first consensus guidelines for haematopoietic SCT (HSCT) in autoimmune diseases (ADs) were published, while an international coordinated clinical programme was launched. These guidelines provided broad principles for the field over the following decade and were accompanied by comprehensive data collection in the European Group for Blood and Marrow Transplantation (EBMT) AD Registry. Subsequently, retrospective analyses and prospective phase I/II studies generated evidence to support the feasibility, safety and efficacy of HSCT in several types of severe, treatment-resistant ADs, which became the basis for larger-scale phase II and III studies. In parallel, there has also been an era of immense progress in biological therapy in ADs. The aim of this document is to provide revised and updated guidelines for both the current application and future development of HSCT in ADs in relation to the benefits, risks and health economic considerations of other modern treatments. Patient safety considerations are central to guidance on patient selection and HSCT procedural aspects within appropriately experienced and Joint Accreditation Committee of International Society for Cellular Therapy and EBMT accredited centres. A need for prospective interventional and non-interventional studies, where feasible, along with systematic data reporting, in accordance with EBMT policies and procedures, is emphasized.
Keywords: Autoimmune Diseases; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; European Union; Female; Hematopoietic Stem Cell Transplantation; Humans; Male; Risk Factors; Safety; Severity of Illness Index

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

The active Zot domain (aa 288-293) increases ZO-1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO-1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation. - Goldblum, Simeon E; Rai, Usha; Tripathi, Amit; Thakar, Manjusha; De Leo, Luigina; Di Toro, Nicola; Not, Tarcisio; Ramachandran, Rithwik; Puche, Adam C; Hollenberg, Morley D; Fasano, Alessio (FASEB J, 2011)
Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activated receptor (PAR)(2)-expressing and PAR(2)-null cells established AT1002 activity to be PAR(2) dependent. Coincident with the increased intestinal permeability, confocal microscopy of AT1002-exposed rat intestinal IEC6 cells revealed displacement of ZO-1 and occludin from intercellular boundaries. In coimmunoprecipitation assays, AT1002 decreased ZO-1-occludin and ZO-1-claudin 1 interactions coincident with PKCα-dependent ZO-1 serine/threonine phosphorylation. Further, AT1002 increased serine phosphorylation of myosin 1C and, at the same time, transiently diminished its association with ZO-1. The COOH-terminal domain of ZO-1 was required for its association with myosin 1C. These data indicate that the NH(2)-terminal portion of active Zot contains a PAR(2)-activating motif, FCIGRL, that increases PKCα-dependent ZO-1 and myosin 1C serine/threonine phosphorylation. These modifications provoke selective disengagement of ZO-1 from its binding partners, occludin, claudin 1, and myosin 1C, coincident with opening of tjs.
Keywords: Amino Acid Sequence; Animals; Caco-2 Cells; Cell Line; Cells, Cultured; Cholera Toxin; Epithelial Cells; Humans; Immunoblotting; Male; Membrane Proteins; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Myosins; Oligopeptides; Phosphoproteins; Phosphorylation; Protein Binding; Protein Kinase C-alpha; Rats; Rats, Wistar; Receptor, PAR-2; RNA Interference; Serine; Threonine; Tight Junctions; Zonula Occludens-1 Protein

ESPGHAN's 2008 recommendation for early introduction of complementary foods: how good is the evidence? - Cattaneo, Adriano; Williams, Carol; Pallás-Alonso, Carmen Rosa; Hernández-Aguilar, Maria Teresa; Lasarte-Velillas, Juan José; Landa-Rivera, Leonardo; Rouw, Elien; Pina, Mónica; Volta, Alessandro; Oudesluys-Murphy, Anne Marie (Matern Child Nutr, 2011)
Since 2002, the World Health Organization and many governments and professional associations have recommended exclusive breastfeeding for 6 months followed by complementary feeding (giving solid foods alongside breast milk) as optimal infant feeding practice. Several articles have been published challenging this recommendation. Arguably, the most influential has been the 2008 commentary of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) Committee on Nutrition, which recommended that complementary foods should be introduced to all infants between 17 and 26 weeks. We challenge the validity of ESPGHAN's position, questioning the adequacy of the literature search, the interpretation and evidence used to reach their conclusions and the balance of an approach that focuses on disease prevention, with scant consideration of growth and neuromotor development. We contend that ESPGHAN's position should be understood as an expert opinion that may be influenced by conflicts of interest. In our view, the ESPGHAN position paper is not evidence based and does not justify a change of the current public health recommendation for 6 months of exclusive breastfeeding. At an individual level, health professionals should understand that developmental readiness for starting solid foods has an age range like other developmental milestones; that fewer infants will probably be ready to start complementary feeding before, rather than after, 6 months; and that their role is to equip parents with the confidence and skills to recognise the signs of developmental readiness. This empowerment process for infants and parents should be preferred over the prescriptive ESPGHAN approach.
Keywords: Breast Feeding; Evidence-Based Practice; Humans; Infant; Infant Food; Infant Nutritional Physiological Phenomena; Milk, Human; Nutritional Status; Public Health; Reproducibility of Results; World Health Organization

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

"GINEXMAL RCT: Induction of labour versus expectant management in gestational diabetes pregnancies". - Maso, Gianpaolo; Alberico, Salvatore; Wiesenfeld, Uri; Ronfani, Luca; Erenbourg, Anna; Hadar, Eran; Yogev, Yariv; Hod, Moshe (BMC Pregnancy Childbirth, 2011)
BACKGROUND: Gestational diabetes (GDM) is one of the most common complications of pregnancies affecting around 7% of women. This clinical condition is associated with an increased risk of developing fetal macrosomia and is related to a higher incidence of caesarean section in comparison to the general population. Strong evidence indicating the best management between induction of labour at term and expectant monitoring are missing. METHODS/DESIGN: Pregnant women with singleton pregnancy in vertex presentation previously diagnosed with gestational diabetes will be asked to participate in a multicenter open-label randomized controlled trial between 38+0 and 39+0 gestational weeks. Women will be recruited in the third trimester in the outpatient clinic or in the Day Assessment Unit according to local protocols. Women who opt to take part will be randomized according to induction of labour or expectant management for spontaneous delivery. Patients allocated to the induction group will be admitted to the obstetric ward and offered induction of labour via use of prostaglandins, Foley catheter or oxytocin (depending on clinical conditions). Women assigned to the expectant arm will be sent to their domicile where they will be followed up until delivery, through maternal and fetal wellbeing monitoring twice weekly. The primary study outcome is the Caesarean section (C-section) rate, whilst secondary measurements are maternal and neonatal outcomes. A total sample of 1760 women (880 each arm) will be recruited to identify a relative difference between the two arms equal to 20% in favour of induction, with concerns to C-section rate. Data will be collected until mothers and newborns discharge from the hospital. Analysis of the outcome measures will be carried out by intention to treat. DISCUSSION: The present trial will provide evidence as to whether or not, in women affected by gestational diabetes, induction of labour between 38+0 and 39+0 weeks is an effective management to ameliorate maternal and neonatal outcomes. The primary objective is to determine whether caesarean section rate could be reduced among women undergoing induction of labour, in comparison to patients allocated to expectant monitoring. The secondary objective consists of the assessment and comparison of maternal and neonatal outcomes in the two study arms. .
Keywords: Adolescent; Adult; Cesarean Section; Diabetes, Gestational; Female; Gestational Age; Humans; Intention to Treat Analysis; Labor, Induced; Patient Selection; Pregnancy; Pregnancy Outcome; Research Design; Watchful Waiting; Young Adult

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

Horizontal gaze palsy and progressive scoliosis without ROBO3 mutations. - Abu-Amero, Khaled K; Faletra, Flavio; Gasparini, Paolo; Parentin, Fulvio; Pensiero, Stefano; Alorainy, Ibrahim A; Hellani, Ali M; Catalano, Dario; Bosley, Thomas M (Ophthalmic Genet, 2011)
BACKGROUND: To describe clinical and genetic observations in a patient with horizontal gaze palsy and progressive scoliosis (HGPPS) without identified mutations in the ROBO3 gene. MATERIALS AND METHODS: Neurologic and orthopedic evaluation of the proband; sequencing all exons, exon-intron boundaries, and promoter region of ROBO3 in the proband and his mother. Array CGH was also carried out in the proband and his mother to evaluate possible chromosomal deletion(s) and/or duplication(s). RESULTS: The proband had complete horizontal gaze restriction with full vertical gaze and small amplitude horizontal pendular nystagmus. He also had severe scoliosis and brainstem hypoplasia pathognomonic of HGPPS. However, complete sequencing of ROBO3 twice in both forward and reverse directions did not reveal any mutations. Array CGH investigation revealed no chromosomal abnormalities. CONCLUSIONS: This patient had clinical and neuroimaging characteristics considered pathognomonic of HGPPS and yet did not have ROBO3 mutations. A clinical misdiagnosis is unlikely in the absence of facial weakness (typical of Moebius syndrome), deafness (typical of the HOXA1 spectrum), or mental retardation (typical of other central decussation abnormalities). It is perhaps more likely that a phenotype identical to HGPPS can be caused by abnormalities in ROBO3 splice variant expression, by mutations of a gene other than ROBO3, or by some environmental or epigenetic factor(s) inhibiting the action of ROBO3 or its protein product in the developing brainstem.
Keywords: Child; Humans; Kyphosis; Magnetic Resonance Imaging; Male; Mutation; Ocular Motility Disorders; Oculomotor Nerve Diseases; Pedigree; Receptors, Immunologic; Scoliosis

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Therapeutic approaches in the treatment of juvenile dermatomyositis in patients with recent-onset disease and in those experiencing disease flare: an international multicenter PRINTO study. - Hasija, Rachana; Pistorio, Angela; Ravelli, Angelo; Demirkaya, Erkan; Khubchandani, Raju; Guseinova, Dinara; Malattia, Clara; Canhao, Helena; Harel, Liora; Foell, Dirk; Wouters, Carine; De Cunto, Carmen; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To evaluate response to therapy over a 24-month period in a large prospective international cohort of patients with juvenile dermatomyositis (DM). METHODS: The study included 145 patients with recent-onset juvenile DM and 130 juvenile DM patients experiencing disease flare, all of whom were <18 years old. Disease activity parameters and therapeutic approaches in 4 geographic areas were analyzed at baseline and at 6, 12, and 24 months. Response was assessed according to the Pediatric Rheumatology International Trials Organization (PRINTO) juvenile DM response criteria, and data were reported "as observed" and in the intent-to-treat (ITT) population. RESULTS: Patients with recent-onset juvenile DM at baseline had higher baseline disease activity and greater improvement over 24 months when compared to juvenile DM patients experiencing disease flare at baseline. Methotrexate (MTX) or high-dose corticosteroids were administered more frequently to patients with recent-onset juvenile DM, compared to juvenile DM patients experiencing disease flare, who were more likely to receive cyclosporine. Compared to patients from Western and Eastern Europe, a higher proportion of patients from South and Central America and North America received pulse steroids, and the average steroid dosage was higher in the North American and South and Central American patients. The use of MTX was similar in all 4 regions, while cyclosporin A was more frequently used in Western Europe. In the "as observed" analysis, 57.9% of the patients with recent-onset juvenile DM and 36.4% of the patients experiencing disease flare (P<0.001) reached at least a 70% response by PRINTO criteria at 6 months; these proportions had increased at month 24 to 78.4% and 51.2%, respectively (P<0.001). Corresponding results of the ITT analysis were much lower, with only one-third of the patients able to maintain the initial assigned therapy over 24 months. CONCLUSION: Patients with recent-onset juvenile DM are more likely to achieve significant clinical improvement over 24 months, when compared to patients experiencing flares of juvenile DM. Internationally, various therapeutic approaches are used to treat this disease.
Keywords: Adolescent; Adrenal Cortex Hormones; Child; Dermatologic Agents; Dermatomyositis; Female; Humans; Longitudinal Studies; Male; Methotrexate; Prospective Studies; Treatment Outcome

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

A case of lymphedema-distichiasis syndrome carrying a new de novo frameshift FOXC2 mutation. - Fabretto, Antonella; Shardlow, Alison; Faletra, Flavio; Lepore, Loredana; Hladnik, Uros; Gasparini, Paolo (Ophthalmic Genet, 2010)
PURPOSE: Lymphedema-Distichiasis (LD, OMIM 153400) is an autosomal dominant disorder with variable expression. The mutated gene implicated is FOXC2, which encodes for a forkhead transcription factor involved in the development of the lymphatic and vascular system. LD is characterized by late childhood or pubertal onset lymphedema of the limbs and distichiasis. Other associations have been reported, including congenital heart disease, ptosis, scoliosis. CONCLUSIONS: Here we describe a case of LD carrying a de novo frameshift mutation of FOXC2 who presented a prepubertal onset of lower limbs lymphedema and mild distichiasis associated with other anomalies such as webbing neck and ptosis.
Keywords: Abnormalities, Multiple; Adolescent; Eye Abnormalities; Eyelashes; Face; Forkhead Transcription Factors; Frameshift Mutation; Humans; Lymphedema; Male; Syndrome

Development of paediatric quality of inpatient care indicators for low-income countries - A Delphi study. - Ntoburi, Stephen; Hutchings, Andrew; Sanderson, Colin; Carpenter, James; Weber, Martin; English, Mike (BMC Pediatr, 2010)
BACKGROUND: Indicators of quality of care for children in hospitals in low-income countries have been proposed, but information on their perceived validity and acceptability is lacking. METHODS: Potential indicators representing structural and process aspects of care for six common conditions were selected from existing, largely qualitative WHO assessment tools and guidelines. We employed the Delphi technique, which combines expert opinion and existing scientific information, to assess their perceived validity and acceptability. Panels of experts, one representing an international panel and one a national (Kenyan) panel, were asked to rate the indicators over 3 rounds and 2 rounds respectively according to a variety of attributes. RESULTS: Based on a pre-specified consensus criteria most of the indicators presented to the experts were accepted: 112/137(82%) and 94/133(71%) for the international and local panels respectively. For the other indicators there was no consensus; none were rejected. Most indicators were rated highly on link to outcomes, reliability, relevance, actionability and priority but rated more poorly on feasibility of data collection under routine conditions. There was moderate to substantial agreement between the two panels of experts. CONCLUSIONS: This Delphi study provided evidence for the perceived usefulness of most of a set of measures of quality of hospital care for children proposed for use in low-income countries. However, both international and local experts expressed concerns that data for many process-based indicators may not currently be available. The feasibility of widespread quality assessment and responsiveness of indicators to intervention should be examined as part of continued efforts to improve approaches to informative hospital quality assessment.
Keywords: Child; Child, Hospitalized; Delphi Technique; Developing Countries; Expert Testimony; Female; Humans; Inpatients; Male; Pediatrics; Quality Indicators, Health Care; World Health Organization

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Incidence of bacteremias and invasive mycoses in children with acute non-lymphoblastic leukemia: results from a multi-center Italian study. - Castagnola, Elio; Rossi, Mario R; Cesaro, Simone; Livadiotti, Susanna; Giacchino, Mareva; Zanazzo, Giulio; Fioredda, Francesca; Beretta, Chiara; Ciocchello, Francesca; Carli, Modesto; Putti, Maria Caterina; Pansini, Valeria; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: Data on the epidemiology of bacteremias and invasive fungal diseases (IFD) in children with acute myeloid leukemia (AML) are scarce. DESIGN AND METHODS: In a multi-center, retrospective study, we analyzed proportion, rate per 1,000 person-days at risk, and cumulative risk of bacteremias and IFD in children with AML. RESULTS: Between January 1998 and December 2005, 240 children were treated for AML at 8 Italian Centers, for a total of 521 treatment courses and 63,232 person-days at risk. Bacteremia was observed in 32% of treatment courses and IFD was seen in 10% (P < 0.0001), with rates of 2.62 and 0.84, respectively (P < 0.001). There was a significantly higher frequency of IFD during relapse treatment: proportion 15% versus 9% (P = 0.05), rate 2.10 versus 0.64 (P = 0.008) and cumulative risk 32% versus 12% (P = 0.007), while there were no differences in the proportion, rate and cumulative risk of bacteremia during front-line or relapse treatment. The epidemiology of bacteremias and IFD was different during front-line therapy for M3 as compared to other types of AML, but the differences were not statistically significant. CONCLUSIONS: Severe infectious complications are frequent during the treatment of pediatric AML, especially during relapse treatment, and bacteremias are more frequent than IFD.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bacteremia; Child; Female; Follow-Up Studies; Humans; Incidence; Italy; Leukemia, Myeloid, Acute; Male; Mycoses; Neoplasm Recurrence, Local; Retrospective Studies

MYH9-related disease: Report on five German families and description of a novel mutation. - Savoia, Anna; Germeshausen, Manuela; De Rocco, Daniela; Henschel, Bettina; Kratz, Christian P; Kuhlen, Michaela; Rath, Bettina; Steuhl, Klaus-Peter; Wermes, Cornelia; Ballmaier, Matthias (Ann Hematol, 2010)
Keywords: Adult; Aged; Child; Chromosome Disorders; DNA Mutational Analysis; Germany; Humans; Infant; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Young Adult

Predictors of poor response to methotrexate in polyarticular-course juvenile idiopathic arthritis: analysis of the PRINTO methotrexate trial. - Vilca, Iris; Munitis, Pablo Garcia; Pistorio, Angela; Ravelli, Angelo; Buoncompagni, Antonella; Bica, Blanca; Campos, Lucia; Häfner, Renate; Hofer, Michael; Ozen, Seza; Huemer, Christian; Bae, Sang Cheol; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To determine whether baseline demographic, clinical, articular and laboratory variables predict methotrexate (MTX) poor response in polyarticular-course juvenile idiopathic arthritis. METHODS: Patients newly treated for 6 months with MTX enrolled in the Paediatric Rheumatology International Trials Organization (PRINTO) MTX trial. Bivariate and logistic regression analyses were used to identify baseline predictors of poor response according to the American College of Rheumatology pediatric (ACR-ped) 30 and 70 criteria. RESULTS: In all, 405/563 (71.9%) of patients were women; median age at onset and disease duration were 4.3 and 1.4 years, respectively, with anti-nuclear antibody (ANA) detected in 259/537 (48.2%) patients. With multivariate logistic regression analysis, the most important determinants of ACR-ped 70 non-responders were: disease duration > 1.3 years (OR 1.93), ANA negativity (OR 1.77), Childhood Health Assessment Questionnaire (CHAQ) disability index > 1.125 (OR 1.65) and the presence of right and left wrist activity (OR 1.55). Predictors of ACR-ped 30 non-responders were: ANA negativity (OR 1.92), CHAQ disability index > 1.14 (OR 2.18) and a parent's evaluation of child's overall well-being < or = 4.69 (OR 2.2). CONCLUSION: The subgroup of patients with longer disease duration, ANA negativity, higher disability and presence of wrist activity were significantly associated with a poorer response to a 6-month MTX course.
Keywords: Adolescent; Antibodies, Antinuclear; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Disability Evaluation; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Male; Methotrexate; Prognosis; Treatment Outcome

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Toward a consensus on guiding principles for health systems strengthening. - Swanson, Robert C; Bongiovanni, Annette; Bradley, Elizabeth; Murugan, Varnee; Sundewall, Jesper; Betigeri, Arvind; Nyonator, Frank; Cattaneo, Adriano; Harless, Brandi; Ostrovsky, Andrey; Labonté, Ronald (PLoS Med, 2010)
Keywords: Global Health; Humans; Public Health

Two cases of Noonan syndrome with severe respiratory and gastroenteral involvement and the SOS1 mutation F623I. - Fabretto, Antonella; Kutsche, Kerstin; Harmsen, May-Britt; Demarini, Sergio; Gasparini, Paolo; Fertz, Maria Cristina; Zenker, Martin (Eur J Med Genet, 2010)
Noonan syndrome (NS) is an autosomal dominant, inherited disorder characterized by facial dysmorphism, congenital heart defects, and reduced postnatal growth. Dysregulated RAS-MAPK signalling is the common molecular basis for NS, a genetically heterogeneous disease. Germline mutations in genes encoding small GTPases of the RAS family (KRAS and NRAS), modulators of RAS function (PTPN11, SOS1 and SHOC2) or downstream signal transducers (RAF1) are causative for NS. SOS1 is the second major gene for NS after PTPN11. Compared to patients with mutations in other genes, SOS1 mutation-positive individuals in general tend to have a more favorable outcome, with less short stature and cognitive impairment. We describe two unrelated patients with NS carrying the same heterozygous SOS1 missense mutation (c.1867T > A/p.F623I). The phenotype of both patients is remarkable as they show uncommon clinical features such as pulmonary lymphangiectasis, congenital pleural effusions, severe feeding problems, and laryngomalacia. These findings may be related to the specific mutation present in our two patients, or be part of the SOS1 phenotype. Detailed clinical assessment of large cohorts of patients with NS and SOS1 mutation is required to clarify this initial observation.
Keywords: Child, Preschool; Genes, ras; Germ-Line Mutation; Heterozygote; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Noonan Syndrome; Phenotype; SOS1 Protein

Atomic models for the polypeptide backbones of myohemerythrin and hemerythrin. - Hendrickson, W A; Ward, K B (Biochem Biophys Res Commun, 1975)
Keywords: Animals; Cnidaria; Computers; Hemerythrin; Metalloproteins; Models, Molecular; Muscle Proteins; Protein Conformation; Species Specificity

Effect of chloroquine on cultured fibroblasts: release of lysosomal hydrolases and inhibition of their uptake. - Wiesmann, U N; DiDonato, S; Herschkowitz, N N (Biochem Biophys Res Commun, 1975)
Keywords: Biological Transport; Cells, Cultured; Cerebroside-Sulfatase; Chloroquine; Dextrans; Fibroblasts; Glucuronidase; Humans; Leukodystrophy, Metachromatic; Lysosomes; Pinocytosis; Skin; Sulfatases